Synaptic Impairment in Layer 1 of the Prefrontal Cortex Induced by Repeated Stress During Adolescence is Reversed in Adulthood - Negrón-Oyarzo, Ignacio; Dagnino-Subiabre, Alexies; Muñoz Carvajal, Pablo (Frontiers in Cellular Neuroscience, 2015)
Chronic stress is a risk factor for the development of psychiatric disorders, some of which involve dysfunction of the prefrontal cortex (PFC). There is a higher prevalence of these chronic stress-related psychiatric disorders during adolescence, when the PFC has not yet fully matured. In the present work we studied the effect of repeated stress during adolescence on synaptic function in the PFC in adolescence and adulthood. To this end, adolescent Sprague-Dawley rats were subjected to seven consecutive days of restraint stress. Afterward, both synaptic transmission and short- and long-term synaptic plasticity were evaluated in layer 1 of medial-PFC (mPFC) slices from adolescent and adult rats. We found that repeated stress significantly reduced the amplitude of evoked field excitatory postsynaptic potential (fEPSP) in the mPFC. Isolation of excitatory transmission reveled that lower-amplitude fEPSPs were associated with a reduction in AMPA/kainate receptor-mediated transmission. We also found that repeated stress significantly decreased long-term depression (LTD). Interestingly, AMPA/kainate receptor-mediated transmission and LTD were recovered in adult animals that experienced a three-week stress-free recovery period. The data indicates that the changes in synaptic transmission and plasticity in the mPFC induced by repeated stress during adolescence are reversed in adulthood after a stress-free period.